2015
DOI: 10.1590/0047-2085000000069
|View full text |Cite
|
Sign up to set email alerts
|

Inserção no mercado de trabalho e uso de drogas entre escolares de duas cidades de médio porte do sul do Brasil

Abstract: Objetivo O início do consumo de drogas ocorre, geralmente, na adolescência. Entre os fatores associados a esse comportamento, está o trabalho. Este artigo analisa a associação entre a inserção no mercado de trabalho e o uso no ano de álcool, tabaco, maconha e cocaína, em uma amostra de 1.961 escolares de dois municípios de médio porte do Rio Grande do Sul. Métodos Foram estimadas razões de prevalência brutas e ajustadas, primeiramente, para sexo e idade e, posteriormente, para sexo, idade e supervisão do uso d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Conversely, the repeated cross-sectional National School Health Survey (n = 109,104-125,123) showed an increasing prevalence of past-month cannabis use among primary and secondary students (ninth grade or 13-17 years) from 2.5% (2012), 4.1% (2015) and 5.3% (2019), including consistently higher rates among males and publicschool students, and in the south/southeast regions of Brazil [40][41][42]. In addition to national studies, regional (e.g., city-or state-based sample) surveys focusing on public and/or private school samples involving youth (5th-12th grade or 10-21 years)-mostly from Brazil's (most populous) state of São Paulo-identified rates of 0.6%-23.5% for lifetime, 0.2%-19% for past-year and 0.3%-10.0% for past-month cannabis use in 2005-2019 (n = 126-7176) [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Use Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the repeated cross-sectional National School Health Survey (n = 109,104-125,123) showed an increasing prevalence of past-month cannabis use among primary and secondary students (ninth grade or 13-17 years) from 2.5% (2012), 4.1% (2015) and 5.3% (2019), including consistently higher rates among males and publicschool students, and in the south/southeast regions of Brazil [40][41][42]. In addition to national studies, regional (e.g., city-or state-based sample) surveys focusing on public and/or private school samples involving youth (5th-12th grade or 10-21 years)-mostly from Brazil's (most populous) state of São Paulo-identified rates of 0.6%-23.5% for lifetime, 0.2%-19% for past-year and 0.3%-10.0% for past-month cannabis use in 2005-2019 (n = 126-7176) [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Use Prevalencementioning
confidence: 99%
“…Cross-sectional studies showed associations of cannabis use with drug trafficking and homicidal conduct among adults (aOR: 3 and 2.8, both p < 0.05, n = 274) [132], and anti-social behaviours (e.g., criminal justice system problems and/or drug trafficking) (p < 0.05), violent behaviour (OR: 4-7, p < 0.001) as well as employment status (RP: 1.35, p = 0.049) among youth-student samples (14-19 years, n = 1961-7176) [43,47,48]. Among women, 9-in-10 (89%) patients with past-year cannabis use in a basic health unit in Piauí state (n = 369) had experienced intimate partner violence; individuals whose partners also used cannabis had higher odds of experiencing intimate partner violence (aOR: 4.7, p = 0.012) [133].…”
Section: Social Outcomesmentioning
confidence: 99%
“…É possível afirmar que os adolescentes que exercem atividade remunerada possuem maior disponibilidade financeira , aumentando a chance de aquisição de bebidas alcoólicas e frequentar lugares como bares, boates e festas, em que ocorre uma exposição maior a esta substância. (91,92,93,94) O fato do trabalho influenciar no consumo de álcool é notado com mais clareza quando se analisa o consumo de álcool antes e após a exposição ao trabalho: mesmo não sendo estatisticamente significante, o número de adolescentes que começaram a consumir álcool após o contato com o trabalho praticamente dobrou.…”
Section: Diretrizes Europeias Para O Manejo Da Hipertensão Arterial E...unclassified